2015
DOI: 10.1111/pbi.12348
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide survey of artificial mutations induced by ethyl methanesulfonate and gamma rays in tomato

Abstract: SummaryGenome‐wide mutations induced by ethyl methanesulfonate (EMS) and gamma irradiation in the tomato Micro‐Tom genome were identified by a whole‐genome shotgun sequencing analysis to estimate the spectrum and distribution of whole‐genome DNA mutations and the frequency of deleterious mutations. A total of ~370 Gb of paired‐end reads for four EMS‐induced mutants and three gamma‐ray‐irradiated lines as well as a wild‐type line were obtained by next‐generation sequencing technology. Using bioinformatics analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
121
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 49 publications
14
121
1
1
Order By: Relevance
“…Indeed, the mutagenesis-induced SNPs are later used as polymorphic markers to map the causal mutation. It has been reported that a typical cv Micro-Tom EMS mutant plant typically carries 2,000 to 4,000 SNPs (Shirasawa et al, 2016).…”
Section: Identification Of the Causal Mutation Underlying A Fruit Brimentioning
confidence: 99%
“…Indeed, the mutagenesis-induced SNPs are later used as polymorphic markers to map the causal mutation. It has been reported that a typical cv Micro-Tom EMS mutant plant typically carries 2,000 to 4,000 SNPs (Shirasawa et al, 2016).…”
Section: Identification Of the Causal Mutation Underlying A Fruit Brimentioning
confidence: 99%
“…Inducing mutations by chemical and physical methods is a highly efficient approach to increase genetic diversity (Shirasawa et al, 2016). Mutants are also potential materials for breeding new cultivar (Takagi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The types of EMS-induced mutation include SNV (base transition, base insertion, and base deletion), CNV, and indel section. The C/G to T/A transitions are the predominant mutations in EMS mutants (Uchida et al, 2011; Henry et al, 2014; Tsuda et al, 2015; Shirasawa et al, 2016). These mutations affect the protein synthesis or structure, thereby leading to phenotypic change.…”
Section: Introductionmentioning
confidence: 99%
“…Henry et al (2014) analyzed mutations in EMS-derived mutant progenies of rice and wheat by using multiplexed global exome capture and sequencing coupled with bioinformatics tools and detected ~18,000 induced mutations. In EMS induced and gamma ray induced mutants of tomato, whole-genome shotgun sequencing analysis was used to calculate the spectrum and distribution of DNA mutations at genome level in the Micro-Tom genome (Shirasawa et al, 2016). The authors found that major mutations in the EMS mutants were C/G to T/A transitions type, while in the gamma-ray mutants, mutations were C/G to T/A transitions, A/T to T/A transversions and A/T to G/C transitions.…”
Section: Muta-genomics Toolsmentioning
confidence: 99%